Transition to complete synchronization in phase-coupled oscillators with nearest neighbor coupling - El-Nashar, Hassan F.; Muruganandam, Paulsamy; Ferreira, Fernando F.; Cerdeira, Hilda A. [UNESP] (American Institute of Physics (AIP), 2009)
We investigate synchronization in a Kuramoto-like model with nearest neighbor coupling. Upon analyzing the behavior of individual oscillators at the onset of complete synchronization, we show that the time interval between bursts in the time dependence of the frequencies of the oscillators exhibits universal scaling and blows up at the critical coupling strength. We also bring out a key mechanism that leads to phase locking. Finally, we deduce forms for the phases and frequencies at the onset of complete synchronization.
Keywords: chaos; nonlinear dynamical systems; synchronisation